A netnographic analysis of prospective international students' decision-making process: implications for institutional branding of American universities in the emerging markets. Issue 2 (2nd July 2016) - Gai, Lili; Xu, Chunhao; Pelton, Lou E.
ABSTRACT: The enrollment of international students (e.g. students admitted using a F-1 visa into the U.S.) has been increasing continually for the past six academic years in American higher educational institutions. This article explores how Chinese applicants make decisions during their application journey for Master's degree programs in business schools. The study employs a netnographic approach to analyse user-generated content posted in one virtual consumer forum. The findings show that Chinese students not only use this forum for school information and alumni reviews, but they also collect suggestions from fellow applicants in their decision-making process. The findings also offer managerial implications for American universities, articulating how institutions of higher education should use proactive institutional branding to attract graduate students from one of the most coveted target markets: the People's Republic of China. The effective use of marketing communications via online websites coupled with offline recruitment fairs demonstrate how universities must embrace omnichannel marketing in their institutional branding.